Exploring The Role of Effective Use of AI In Improving Strategic Performance Under the Digital Transformation of Higher Education Institutions - Almusawy, Azhar Mohammed Ridh (Journal of Ecohumanism, 2025)
This study aims to diagnose the role of the effective use of Artificial Intelligence (EFUS) in enhancing strategic performance (STPE) within the context of digital transformation in higher education institutions. Grounded in the Theory of Effective Use, the research conceptualizes EFUS through key behavioral and system-based dimensions, while STPE is assessed via a balanced set of organizational performance indicators. A quantitative approach was employed using a structured electronic questionnaire administered to a random sample of 243 faculty members at the University of Kufa. Data were analyzed using Structural Equation Modeling to examine the hypothesized relationships between EFUS and STPE. The findings reveal a strong and positive association, emphasizing the strategic importance of moving from basic AI adoption to purposeful and effective integration. The study contributes to the theoretical advancement of effective AI utilization in educational contexts and provides practical guidance for institutional leaders aiming to align technological innovation with long-term strategic objectives. Ethical and governance considerations are also highlighted as critical for the responsible use of AI in higher education.